Design Through Landscape Architecture for Residential Common Spaces in Japan - Kader, sherko Karim; Ibrahim Agha, Shava Shirwan; Qadir, Sham Mustafa; Muhealdeen, Banaz N. (Kurdistan Journal of Applied Research, 2022)
Landscape architecture focuses on studying and designing indoor and outdoor environments. It entails the elements of architecture, art, engineering, and other sociological factors. Accordingly, the landscape architects design the spaces buildings that give life to the structures. Landscape architecture is visible in parks, streets, shared paths, plazas. Shopping malls, apartment compounds, transport networks, and gardens are also examples of landscape architecture. Furthermore, the works of landscape architecture are also visible in museums, memorials, cemeteries, universities, and other schools. Modern architects have designed different permanent structures that will stand for a long period of time. Notwithstanding the preceding, the discourse on what qualifies as landscape architecture and what does not is yet to be settled. This discussion elucidates the process of research through design in landscape architecture, the literature regarding the field, and conducts a case study of specific landscape architecture to elicit applicability of the enumerated concepts. Moreover, the discourse also reveals the research method utilized in the case study and the results as well and discussion.